Meaning and Truth in 2 Corinthians - Cmi, Paul Kalluveettil (Journal of Dharma, 1990)
This book was first published in the United Kingdom in 1987 by SPCK, London in the series "Biblical Foundations in Theology" edited by James D. G. Dunn and James P. Mackey. The series was planned to bridge the gap between biblical scholarship and the larger enterprise of Christian theology. The editors had in mind to make "a distinctive and .constructive contribution to current concerns about how, in the modern world, Christianity is to be lived as well as understood."